PSYCHOLOGY OF PRESCHOOL CHILDREN AND ITS STATUS OF LEARNING. - Ismoilova Sabina Erkin qizi (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2023)
The article discusses the state of research on the psychology of preschool children and the necessary recommendations for them. The psychology of preschool children and the reasons for their learning are studied and analyzed, and information is given about ways to eliminate them.